Se suspendre aux lendemains de Fessenheim – une approche croisée sur les traces visibles et invisibles d’un territoire nucléaire en transformation. - Élise Alloin; Florence Fröhlig (VertigO)
In 2020 the two reactors at Fessenheim Nuclear Power Plant were eventually shut down. However, regional and transnational debates about the site’s reconversion that flourished ever since have failed to consider this nuclear power plant's material and immaterial value for the region.We pursued an action-participatory research frame to address this gap, combining ethnological analytical methodology with artistic practices. This research allowed initiating a reflection on the imprint of this nuclear power plant in the region's cultural, natural, and mental landscape. This article presents four audience-specific meeting devices: an introductory exhibition, a round table, a postcard, and an event for schoolchildren. These were developed to raise awareness about the issue at stake and to collect the imaginaries that this power station has left among the people concerned.These participatory action-research devices, carried out over almost a year, made it possible to open dialogue and raise awareness among a public that is generally reluctant to engage with the material and immaterial value of the plant in the region. The meeting devices helped to bring different imaginaries and associations to the surface, yet only certain expressions could be collected as part of personal experiences concerning the plant. Nevertheless, this interaction between an artist, an ethnologist, and an audience has proven to be an effective method to knowledge co-production. Moreover, it started a form of public engagement that other actors may build on to continue the process of reflection initiated by this introductory exhibition.